MSME Product Innovation Strategy in Facing Global CompetitioninMakassar City - Zainal, Henni; Mahmud, Muh Nasir (Universitas Negeri Makassar, 2025)
This study aims to identify and analyze the strategies implemented by MSMEs in Makassar City in facing global competition. The main focus of this study is how MSMEs adopt innovation in products, digital marketing, and human resource capacity building to increase competitiveness and business sustainability. The research method used is a mixed-method approach, with data collection through literature studies, analysis of official documents, and reports from the Cooperatives and MSMEs Office regarding MSME growth trends from 2021 to 2023. The results show that product innovation strategies, the use of digital technology in marketing, and access to capital through partnerships with financial institutions contribute to MSME growth, as reflected in the increase in the number of developing businesses from 34% in 2021 to 71% in 2023. However, challenges such as low digital literacy, limited access to international markets, and intense competition with global products remain major obstacles. To strengthen the competitiveness of MSMEs, synergy is needed between the government, academia, and the private sector in providing training, mentoring, and more inclusive access to financing. The results of this study indicate that innovation supported by a conducive business ecosystem can increase the competitiveness of MSMEs in Makassar City and simultaneously stimulate local economic growth. Recommendations are provided for strengthening digitalization-based policies and economic inclusion to support MSME development.